2013
DOI: 10.1002/qua.24428
|View full text |Cite
|
Sign up to set email alerts
|

H2S splitting on Cu(110): Insight from combined periodic density functional theory calculations and microkinetic simulation

Abstract: Practical copper (Cu)‐based catalysts for the water–gas shift (WGS) reaction was long believed to expose a large proportion of Cu(110) planes. In this work, as an important first step toward addressing sulfur poisoning of these catalysts, the detailed mechanism for the splitting of hydrogen sulfide (H2S) on the open Cu(110) facet has been investigated in the framework of periodic, self‐consistent density functional theory (DFT‐GGA). The microkinetic model based on the first‐principles calculations has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Previous studies normally report the preferred sulfur adsorption binding site, the binding (adsorption) energy, the sulfur-surface interatomic distances, and the diffusion energy of sulfur. The preferred adsorption site and the binding energy have been reported for sulfur on Ni(111), 3,9,17,28,30,31 Cu(111), 9,[13][14][15]17,25,26,31,35 Rh(111), 17 Pd(111), 4,15,22,26,35 Ag(111), 2,15,17,25,35 Ir(111), 34 Pt(111), 4,17,37 Au(111), 15,16,22,26 Ni(110), 9 Cu(110), 5,9,13 Au(110), 21 Ni(100), 9,12,30 Cu(100), 9,12,14 Ir(100), 29 Au(100), 7,16 Pd(211), 36 and Au(211). 16 Th...…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies normally report the preferred sulfur adsorption binding site, the binding (adsorption) energy, the sulfur-surface interatomic distances, and the diffusion energy of sulfur. The preferred adsorption site and the binding energy have been reported for sulfur on Ni(111), 3,9,17,28,30,31 Cu(111), 9,[13][14][15]17,25,26,31,35 Rh(111), 17 Pd(111), 4,15,22,26,35 Ag(111), 2,15,17,25,35 Ir(111), 34 Pt(111), 4,17,37 Au(111), 15,16,22,26 Ni(110), 9 Cu(110), 5,9,13 Au(110), 21 Ni(100), 9,12,30 Cu(100), 9,12,14 Ir(100), 29 Au(100), 7,16 Pd(211), 36 and Au(211). 16 Th...…”
Section: Introductionmentioning
confidence: 97%
“…Density Functional Theory (DFT) calculations have been performed to study the adsorption of sulfur on the low-index surfaces of multiple Face Center Cubic (FCC) metals. [3][4][5]7,9,10,[12][13][14][15][16][17]21,22,25,26,[28][29][30][33][34][35][36][37] We surveyed the DFT calculations of sulfur on FCC metal surfaces reported since the year 2000; see Ref. 39 for an account of earlier calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microkinetic Model. Previous theoretical studies of H 2 S splitting on the (111), ( 110), (211), and (311) Cu surfaces 29,30 have all reported that the disproportionation of two SH* molecules to H 2 S* and S* did not open up a pathway responsible for the H−S bond breakage in the SH* intermediate at all, which stems from the expectation of an extremely low surface coverage for SH*. In what follows, therefore, the present microkinetic modeling based on a meanfield treatment was developed only according to a total of four reaction steps implicated in the mechanism of sequential hydrogen removal from H 2 S on Cu(100) and Au(100), i.e., step i with i = 1−4, which are listed as eqs 10−13, respectively:…”
Section: Computational Detailsmentioning
confidence: 99%
“…In reality, the rates of the constituent elementary events are remarkably influenced by the temperature factor. Within all the reported reaction networks, the H 2 recombinative desorption step, 2H* → H 2 + 2*, was also ignored, whose kinetics, however, affects the surface deposition of S* via H 2 S. More seriously, because of the impacts of surface overage upon the dissociation rate, just comparing alone the energy barriers to be overcome to carry out reaction pathways as in the prior theoretical modelings , might be misleading and can not ensure a reliable assessment of their relative ease or difficulty. , Hence, many fundamental puzzles, such as the actual reaction mechanism and equilibrium surface composition in the course of H 2 S decomposition, remain not understood well at the molecular level. To help improve this understanding, the present work showed a comprehensive comparative study of the chemical process leading to atomic sulfur under realistic conditions on the extended (100) facets of pure Cu and Au metals.…”
Section: Introductionmentioning
confidence: 99%